Aspectos físicos e fisiológicos de sementes de Fimbristylis dicothoma relacionados à germinação e dormência - Mendonca, Giovana Soares de [UNESP]; Martins, Cibele Chalita [UNESP]; Martins, Dagoberto [UNESP]; Gomes Lopes, Maria Teresa (Univ Federal Ceara, Dept Geol, 2015)
In the seeds of pioneer plants, the application of treatments for breaking dormancy, and selection by colour and size, are strategies for obtaining seeds of less dormancy and better germination performance. The aim of this study was to evaluate the effect of the physical and physiological aspects of seeds of the tall fringe-rush (Fimbristylis dichotoma) on germination and dormancy. To do this, the seeds were submitted to the following treatments in three studies: (i) control, immersion in H2SO4 (98%, 36N) for 1 minute, immersion in KNO3 (1, 2 and 3%) for 15 minutes, seeding on a substrate moistened with KNO3 (0.2%) and exposure for 5 and 10 hours in a forced air circulation oven at 40 and 70 degrees C; (ii) classification of the seeds by colour (light and dark) and application of the following treatments: control, immersion of the seeds in H2SO4 (98%, 36N) for 1 and 2 minutes, immersion in KNO3 (5% and 10%) for 15 and 30 minutes and seeding on a substrate moistened with KNO3 (0.2%); (iii) classification by size (0.60, 0.50 and 0.40 mm) and germination on a substrate moistened with KNO3 (0.2%) or distilled H2O. The seeds were evaluated by germination test, first count and germination speed index. Moistening the substrate with KNO3 (0.2%), and heat treatment at 40 degrees C for 10 hours improve performance in seeds of the tall fringe-rush. Light-coloured seeds do not display dormancy. Medium-sized seeds of the tall fringe-rush show better performance in terms of percentage and speed of germination.

Em sementes de plantas pioneiras a aplicação de tratamentos de superação de dormência e a seleção por cor e tamanho são estratégias para a obtenção de sementes com menor dormência e melhor desempenho germinativo. O objetivo neste trabalho foi avaliar o efeito de aspectos físicos e fisiológicos de sementes de falso-alecrim-da-praia sobre sua germinação e dormência. Para tanto, as sementes foram submetidas aos seguintes tratamentos em três estudos: (i) testemunha, imersão em H2SO4 (98%, 36N) por 1 minuto, imersão em KNO3 (1; 2 e 3%) por 15 minutos, semeadura em substrato umedecido com KNO3 (0,2%) e exposição por 5 e 10 horas em estufa com circulação forçada de ar a 40 e 70 °C; (ii) classificação das sementes por cor (clara e escura) e aplicação dos seguintes tratamentos: testemunha, imersão das sementes em H2SO4 (98%, 36N) por 1 e 2 minutos, imersão em KNO3 (5% e 10%) por 15 e 30 minutos e semeadura em substrato umedecido com KNO3 (0,2%); (iii) classificação por tamanho (0,60; 0,50 e 0,40 mm) e germinação em substrato umedecido com KNO3 (0,2%) ou H2O destilada. As sementes foram avaliadas por meio do teste de germinação, primeira contagem e índice de velocidade de germinação. O umedecimento do substrato com KNO3 (0,2%) e o tratamento térmico à 40 °C por 10 horas melhoram o desempenho das sementes de falso-alecrim-da-praia. Sementes de cor clara de falso-alecrim-da-praia não apresentam dormência. Sementes de tamanho médio de falso-alecrim-da-praia apresentam melhor desempenho quanto à porcentagem e velocidade de germinação.
Physical and physiological aspects of seeds of Fimbristylis dicothoma as related to germination and dormancy
Keywords: Weed; Tall fringe-rush; Colour; Size; Temperature; Planta daninha; Falso-alecrim-da-praia; Cor; Tamanho; Temperatura